Systematic review of the community environment for physical activity in young people - an update to the Report Card Brazil - Eduardo Rossato de Victo; Dirceu Solé; Gerson Ferrari (Universidade Federal de Santa Catarina, 2021)
The aim of this study was to update a systematic review on the relationship between the environment and physical activity among Brazilian children and adolescents. The search for articles for this review was performed in the MEDLINE, LILACS / BIREME, and SCIELO databases. For this update, only articles published in 2018 and 2019 were used. Descriptors were defined in English and Portuguese. The Boolean used for the advanced search was used, with 3 main blocks: environment, physical activity, and population. Additional filters were used ​​in accordance with the structure of a database. In all, 5 articles were included in this systematic review, 4 with a population-based sample and 1 with a school-based sample. Among the selected studies, 4 were carried out in the southern region of Brazil (2 in Santa Catarina; 1 in Rio Grande do Sul; 1 in Paraná) and the other article was carried out with a national sample. The research period ranged between 2012 and 2017, with a sample size ranging from 38 volunteers to 102,072 participants. The environmental indicators found were road safety, the existence and use of spaces for the practice of physical activity, the characteristics of the school, and the possibility of practice in the school environment. It was concluded that environmental indicators can enhance the practice of physical activity among young Brazilians, requiring public policies that develop environmental projects to promote physical activity.